Utilization of Local Resources with Fermentation Technology as a Feed for Native Chickens - Luh Suariani; Betty Bagau; Jein Rinny Leke; I Gusti Ayu Dewi Seri Rejeki; Ni Ketut Etty Suwitary; Ni Made Yudiastari; Ni Ketut Mardewi; Ni Made Ayu Gemuh Rasa Astit; Ni Ketut Sri Rukmini; Yan Tonga; I Gusti Agus Maha Putra Sanjaya; I Nyoman Kaca; I Gede Sutapa; Yofardo Kundul; Antonius Andi; Agustinus Ngongo Bili; Ignatius Gari Jati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service is carried out to solve problems faced by the community. One of the problems local chicken farmers face is the limited quality of feed resources. Therefore, community service was provided by training on making fermented feed made from local resources as feed for native chickens. This activity was carried out in the Manuk Amerta Group, Asahduren Village, Pekutatan District, Jembrana-Bali.This activity was organized in collaboration with the Faculty of Animal Husbandry UNSRAT Manado. Training activities run well and are helpful in realizing feed independence by utilizing local potential agricultural waste. Mentoring activities are still needed for program sustainability. Fermented feed has better nutritional value and is preferred by livestock to increase livestock production.